Life Cycle Assessment of Fusion Welding Processes—A Case Study of Resistance Spot Welding Versus Laser Beam Welding. Issue 6 (17th May 2022) - Pittner, Andreas; Rethmeier, Michael
Abstract : The high amount of resource consumption of fusion welding processes offers the potential to reduce their environmental impact. While the driving forces are known from a qualitative perspective, the quantitative assessment of the crucial parameters is not a trivial task. Therefore, herein, a welding‐specific methodology to utilize life cycle assessment as a tool for evaluating the environmental impact of fusion welding processes is presented. In this context, two welding processes, resistance spot welding and laser beam welding, are analyzed for two different use cases. These comprise the welding of shear test specimens and a cap profile made of electrogalvanized sheets of DC 05 + ZE (1.0312) as representative of an automotive application. For both welding processes, the main influences on the resulting environmental impact categories are evaluated and compared. The requirements for ecological efficient welding processes are discussed and implemented. Abstract : Herein this research paper, life cycle assessment of fusion welding processes is utilized by developing a methodology that enables the evaluation of relevant impact factors. Resistance spot welding and laser beam welding as industrially widespread welding processes are analyzed with regards to their environmental burdens. The potential and driving forces for a resource‐efficient process design are shown in the results.